2003
DOI: 10.1055/s-2003-42431
|View full text |Cite
|
Sign up to set email alerts
|

A Selective and Mild Oxidation of Primary Amines to Nitriles with Trichloroisocyanuric Acid

Abstract: O x i d a t i o n o f P r i m a r y A m i n e s t o N i t r i l e s w i t h T r i c h l o r o i s o c y a n u r i c A c i d Fen-Abstract: An efficient and highly selective method for the oxidative conversion of primary amines to the corresponding nitriles using trichloroisocyanuric acid in the presence of catalytic TEMPO under mild reaction conditions is described. Other functional groups such as C,C-double bonds, benzyloxy etc. were found to be unaffected under the reaction conditions. This procedure provides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 8 publications
0
27
0
Order By: Relevance
“…Chen and his co-workers reported the oxidation of primary amines into nitriles by TCCA in the presence of a catalytic amount of TEMPO under mild reaction conditions (Scheme 9) [23]. Optimization of the reaction condition showed that the best results were obtained in dichloromethane at 10 ºC and the use of 1 mol% of the catalyst.…”
Section: Methodsmentioning
confidence: 99%
“…Chen and his co-workers reported the oxidation of primary amines into nitriles by TCCA in the presence of a catalytic amount of TEMPO under mild reaction conditions (Scheme 9) [23]. Optimization of the reaction condition showed that the best results were obtained in dichloromethane at 10 ºC and the use of 1 mol% of the catalyst.…”
Section: Methodsmentioning
confidence: 99%
“…10% yield. This interesting observation shows that the laccase-mediator system is capable of oxidizing the initially formed imine intermediate to a nitrile [22], and further oxidizing the primary aldehyde product to a [23]. The concentration of (S) did not change after complete consumption of the benzylamine, but the concentration of (T) did increase (reaching ∼40% yield) at the expense of (Q).…”
Section: Primary Benzyl Aminesmentioning
confidence: 93%
“…The present system was further examined for the direct conversion of aldehydes 3 into nitriles, and the results are summarized in Table 1 (entries [16][17][18][19][20][21][22][23][24]. We obtained a very good conversion irrespective of the electronic nature of the aldehyde.…”
Section: Methodsmentioning
confidence: 99%